PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN NUSANTARA DI PELABUHAN TELAGA PUNGGUR BATAM PADA ERA NEW NORMAL - Ade Sri Anisha Br Sitepu; I Made Sendra; IGPB. Sasrawan Mananda (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
Covid-19 Pandemic impacted in various activites carried out with observe to the principle of 3M. Telaga Punggur Seaport as facilities and infrastructure tourists applied health protocols 3M. in the conditions at the field found out that there are still many tourists who do not obey the regulations such as wearing the masks, and the incompleteness of 3M facilities that causes many complaints from tourists. This study aims to find out the influence of service quality to the satisfaction of Indonesian tourists at Telaga Punggur Seaport. This type of research used in this research is descriptive quantitative technique and using simple linear regression. Data collection technique in this research using observations, interviews, documentation, literature studies, and questionnaires were distributed to 100 domestic tourists who had used Telaga Punggur Seaport in the era of the pandemic Covid-19 pandemic. Sampling techniques using purposive sampling techniques. This study using SPSS 25 as data analysis tool. The results showing that the quality service that consist of tangibles, Reliability, Responsiveness, Assurance, and Emphaty significantly influenced the variable satisfaction of tourists in the amount of 42.4%. The level of quality of service in Telaga Punggur Port is relatively good. Just need to increase the dimensions of physical evidence on the health protocol facility indicators because it is still in the range of sufficient/hesitant. It is expected that Telaga Punggur Seaport improves the quality of service bt adding health protocol tools such as thermo gun, hand sanitizer, and physcal distancing.